Critical Study Of The Concept Of Nasikh Wa Mansukh In A Modern Qur'ani Hermeneutic Perspective - Ahmad Muhaimin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The concept of nasikh wa mansukh in the classical tradition faces serious problems when read through the lens of modern hermeneutics. This concept relies on often uncertain verse dating and variable identification, making it vulnerable to subjectivity. This type of research uses library research. Data sources in this study are classified into two main categories, namely primary and secondary data sources. The data collection technique applied is a library technique (documentary study). The results of the study show that: 1). The deconstruction of the classical epistemology of nasikh wa mansukh is that the epistemological foundation of the classical nasikh wa mansukh concept which rests on a speculative chronology of verse revelation, subjective identification criteria, and the mechanical logic of abrogation turns out to be fragile when deconstructed through modern hermeneutics. 2). Reinterpretation as a process of legal evolution and moral education is that the phenomenon that has been called nasikh wa mansukh has been successfully reinterpreted as a manifestation of a progressive moral education process (al-tadrij) and contextual legal evolution. 3). The implications for ethical reading and the universality of the Qur'an are that this deconstruction brings fundamental implications for interpretation, namely the creation of an approach that places universal ethical values as the main hermeneutical framework.